2019
DOI: 10.3389/fncel.2019.00106
|View full text |Cite
|
Sign up to set email alerts
|

Wheel Running Improves Motor Function and Spinal Cord Plasticity in Mice With Genetic Absence of the Corticospinal Tract

Abstract: Our previous studies showed that mutant mice with congenital absence of the corticospinal tract (CST) undergo spontaneous remodeling of motor networks to partially compensate for absent CST function. Here, we asked whether voluntary wheel running could further improve locomotor plasticity in CST-deficient mice. Adult mutant mice were randomly allocated to a “runners” group with free access to a wheel, or a “non-runners” group with no access to a wheel. In comparison with non-runners, there was a significant mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Exercise training has many metabolic benefits, including plasma lipoprotein and triglyceride (TG) levels [ 18 ], and glycemic control [ 19 ]. Voluntary aerobic exercise prevents ageand high-fat-induced vascular dysfunction, mitochondrial oxidative stress, and inflammation in mice [ 20 ], and improves motor function and spinal cord plasticity [ 21 ]. These benefits could be preserved in those who exercise throughout their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training has many metabolic benefits, including plasma lipoprotein and triglyceride (TG) levels [ 18 ], and glycemic control [ 19 ]. Voluntary aerobic exercise prevents ageand high-fat-induced vascular dysfunction, mitochondrial oxidative stress, and inflammation in mice [ 20 ], and improves motor function and spinal cord plasticity [ 21 ]. These benefits could be preserved in those who exercise throughout their lives.…”
Section: Discussionmentioning
confidence: 99%
“…No. 12183018A, Invitrogen Life Technologies) for whole-genome gene expression analysis according to the previous reports [20]. Brie y, the quality and quantity of the puri ed RNA were assessed using Agilent 2100 Bioanalyzer.The method based on fragments per kilobase of exon per million fragments mapped (FPKM) was used to calculate gene expression.…”
Section: Whole-genome Gene Expression Analysis and Reverse Transcript...mentioning
confidence: 99%
“…The brain was collected into postxed in 4% PFA for 24h and dehydrated with 15% sucrose at 4℃overnight, followed by 30% sucrose at 4℃for 24h. For immuno uorescence, a standard protocol was used with minor modi cations [20]. Brie y, 20µm frozen coronal sections were washed with PBS three times, permeabilized (PBS with 1.5% Triton X-100), blocked (PBS with 10% goat serum plus 3% bovine serum albumin) and incubated with primary antibodies overnight at 4℃.…”
Section: Immunostainingmentioning
confidence: 99%
“…Exercise training aimed at promoting motor function has been studied extensively with SCI patients and animal models [ 9 ]. The biological effects of exercise training mainly include preventing dendritic atrophy of motor neurons [ 10 ], inducing collateral sprouting of axons [ 11 ], reducing myelin loss [ 12 ], and promoting the expressions of neurotrophic factors [ 13 ]. Some studies reported that exercise training is beneficial to improve motor function after SCI [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%